Distribución de un carrascal de Quercus rotundifolia en las Sierras de Carrascoy y El Puerto (SE de España) : estudio comparativo de dos modelos de gestión ambiental - Aledo E.; Esteve M.A.; Ferrer D.; Ramírez L. (Jornadas sobre las bases ecológicas para la gestión en ecosistemas terrestres, 1989)
The study of the distribution of Quercus rotundifolia in the area of the Majal Blanco (Carrascoy and the Puerto Mountains, South-eastern Spain), shows that this species of evergreen oak follows substrate characteristics and the orientation of the terrain. Particularly the abundance of Q. rotundifolia is higher in the metamorphic shads, although it can be found scattered throughout the rest of the areas of the studied zone. These results are substantially different from those found in the Special plan for the protection of Carrascoy and the Puerto Mountains using phytosociologic methods. The last methodology establishes narrow limits for the potential distribution of the Q. rotundifolia and excludes the most important spots of that species. Accordingly, the regulations affecting the use of the land derived from the mentioned protection plan are without value, at least in the area of the Majal Blanco.
Jornadas sobre las Bases Ecológicas para la Gestión en Ecosistemas Terrestres, 1988/06/13-15, Zaragoza (Spain)